UMPSA and Media collaborate to promote healthy lifestyles through ‘Santai Boling’ - Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 22 October 2024 – A total of 80 media practitioners, representatives from local media agencies, and members of the university management participated in the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Friendly Programme with the Media, held at Premium Lanes, Kuantan Plaza.